Answer :

Given, a pair of polynomial as x – 1, x^{3} + 4x^{2} – 3x – 6

Need to find out the first polynomial is factor of second and if not a factor need to find the remainder

⇒ To check x – 1 is a factor of x^{3} + 4x^{2} – 3x – 6 we must substitute x = 1 in the second polynomial, we get as follows

⇒ 1 + 4 – 3 – 6 = – 4 not equal to 0

∴ x – 1 is not a factor of x^{3} + 4x^{2} – 3x – 6

⇒ To find the remainder by using divide second polynomial by first polynomial

⇒ so, we can subtract a number from the second polynomial to get the remainder

∴ x^{3} + 4x^{2} – 3x – 6 = (x – 1)q(x) + c

⇒ x^{3} + 4x^{2} – 3x – 6 –c = (x – 1)q(x)

⇒ c = ((x^{3} + 4x^{2} – 3x – 6) – (x – 1)) × q(x)

⇒ Now, substitute x = 1 in the above equation we get

⇒ c = (1 + 4 – 3 – 6 – 1 + 1) × q(1)

∴ c = – 4

– 4 is the remainder

Rate this question :

In each pair of pKerala Board Mathematics Part-2

In each pair of pKerala Board Mathematics Part-2

What first degreeKerala Board Mathematics Part-2

In each pair of pKerala Board Mathematics Part-2

In each pair of pKerala Board Mathematics Part-2

In each pair of pKerala Board Mathematics Part-2

For each pair of Kerala Board Mathematics Part-2

For each pair of Kerala Board Mathematics Part-2

For each pair of Kerala Board Mathematics Part-2

For each pair of Kerala Board Mathematics Part-2